Gerbang Tertutup dan Terbuka pada Handphone Android Menggunakan Bluetooth - Sri Mulyati; Sumardi Sadi (Sekolah Tinggi Teknik - PLN, 2019)
The problem with opening the gate opening now is to work manually, which is opening and closing as well secure with a key, then pull or push the gate. This is certainly less efficient and less effective because it requires time and energy to do it. One solution is to make a control device it works automatically ie using a microcontroller, Bluetooth, and servo motor, with communication devices Android-based handphone. Laboratory experimental methods have been carried out to make 'open and close tools the gate with a cellphone'. Based on the results of the trial using Bluetooth and mobile phones, this tool can work up to a distance of 11.5 meters with a response time of 1 second. This prototype tool is very cheap, practical, efficient and effective in opening and closing gates. Not all Bluetooth can open and close gates because the password is required for the accent. This prototype is a simulation tool that works well.